2011
DOI: 10.1038/jhg.2011.33
|View full text |Cite
|
Sign up to set email alerts
|

HLA-C, CSTA and DS12346 susceptibility alleles confer over 100-fold increased risk of developing psoriasis: evidence of gene interaction

Abstract: Psoriasis is an inflammatory skin disorder that exhibits multifactorial mode of inheritance. In addition to the well-known susceptibility locus PSORS1 many other loci have been shown to be implicated in the genetic predisposition for disease. However, interactions between loci have not been thoroughly explored. Thus, we measured the effect of potential interaction between human leukocyte antigen (HLA)-C, CSTA and D1S236 at PSORS1, PSORS4 and PSORS5, respectively, in the development of psoriasis. Analysis of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Psoriasis is unique in that sense, as recent publications have provided evidence for genetic interaction between HLA-C*06 and LCE3C_LCE3B-del, and between HLA-C*06 and ERAP1 (de Cid et al, 2009;Strange et al, 2010;Riveira-Munoz et al, 2011;Zheng et al, 2011). In one study, genetic interaction was observed between three loci, HLA-C, CSTA, and D12346 (Vasilopoulos et al, 2011). The interaction between HLA-C*06 and LCE3C_LCE3B-del was first discovered in our Dutch psoriasis case-control cohort but has now been documented for a number of populations (see meta-analysis by Riveira-Munoz et al (2011)).…”
Section: Genetic Interactions In Psoriasismentioning
confidence: 90%
“…Psoriasis is unique in that sense, as recent publications have provided evidence for genetic interaction between HLA-C*06 and LCE3C_LCE3B-del, and between HLA-C*06 and ERAP1 (de Cid et al, 2009;Strange et al, 2010;Riveira-Munoz et al, 2011;Zheng et al, 2011). In one study, genetic interaction was observed between three loci, HLA-C, CSTA, and D12346 (Vasilopoulos et al, 2011). The interaction between HLA-C*06 and LCE3C_LCE3B-del was first discovered in our Dutch psoriasis case-control cohort but has now been documented for a number of populations (see meta-analysis by Riveira-Munoz et al (2011)).…”
Section: Genetic Interactions In Psoriasismentioning
confidence: 90%
“…Cystatin A is known to have antimicrobial properties, is an epidermal protease and a skin barrier gene and is an early differentiation marker of keratinocytes. Interestingly, cystatin A is one of the candidate genes in the PSORS5 susceptibility locus for psoriasis (32); and it has been suggested that the cystatin A risk allele confers a 100-fold increased risk for developing psoriasis (33). The identification of cystatin in lesional mouse skin using an unbiased free label approach provides an added validation of the KCTie2 mouse model and allows us to examine newly identified peptides to determine what their importance may be specifically in human psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus interesting to speculate that increases in CD146+ Tc17 cells in the peripheral circulation are associated with diseases linked to HLA class I rather than class II. Supporting this concept is the finding in a previous study that Tc17 cells are overrepresented in skin lesions of psoriasis patients, a disease in which another class I antigen, HLA-Cw6, is the strongest susceptibility candidate gene (29,30). …”
Section: Discussionmentioning
confidence: 80%